If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(a + -2) + 8(a + -3) = -8 Reorder the terms: 3(-2 + a) + 8(a + -3) = -8 (-2 * 3 + a * 3) + 8(a + -3) = -8 (-6 + 3a) + 8(a + -3) = -8 Reorder the terms: -6 + 3a + 8(-3 + a) = -8 -6 + 3a + (-3 * 8 + a * 8) = -8 -6 + 3a + (-24 + 8a) = -8 Reorder the terms: -6 + -24 + 3a + 8a = -8 Combine like terms: -6 + -24 = -30 -30 + 3a + 8a = -8 Combine like terms: 3a + 8a = 11a -30 + 11a = -8 Solving -30 + 11a = -8 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + 11a = -8 + 30 Combine like terms: -30 + 30 = 0 0 + 11a = -8 + 30 11a = -8 + 30 Combine like terms: -8 + 30 = 22 11a = 22 Divide each side by '11'. a = 2 Simplifying a = 2
| 2y-y+4y-6=0 | | 10x^2y^3z*10xy^4z^3= | | 3d+12=0 | | -7(1+3n)=-7-7n | | 0.5-46=17 | | mn^3*2m^3n*5m^2n^2= | | 4(y-3)=7y | | -x-3.05+0.7x=-5 | | 5x+10=0 | | 2(3t-6)=3t | | 8=10-(5-w) | | 4x^5y^2*x^3y^2= | | -2x-x-1=0 | | -x-2.92+0.6x=-6 | | 8(w+1)-6=26 | | 0.16-2=-9 | | x^5y^2*x^3y^3= | | n-11=6n-11 | | 4x^5y^2*x^3y^3= | | m^2-4m-5=0 | | -11-3x=9-8x | | -8m+3m=35 | | 4z-6=9z-2 | | 2xy^2*3x^2y= | | v^8*2v^4*3v^2= | | 5x+9=-16 | | 9k-3k= | | 4u^2*3u^3*2u= | | s^4*4s^3= | | -39-8v=-5(6v-1) | | 3q^3*2q^5= | | -p*-p*-p= |